Contagion in derivatives markets - Young, H; Paddrik, M; Rajan, S (University of Oxford, 2017)
A major credit shock can induce large intra-day variation margin payments between counterparties in derivatives markets, which may force some participants to default on their payments. These payment shortfalls become amplified as they cascade through the network of exposures. Using detailed DTCC data we model the full network of exposures, the shock-induced payments, the initial margin collected, and liquidity buffers for about 900 firms operating in the U.S. credit default swaps market. We estimate the total amount of contagion, the marginal contribution of each firm to contagion, and the number of defaulting firms for credit shocks of different magnitudes. A novel feature of the model is that it allows for a range of possible responses to balance sheet stress, including delayed or partial payments. These 'soft default' options distinguish our approach from conventional network models, which typically assume that full default is triggered whenever the default boundary is breached. Revised January 2018